2008
DOI: 10.1001/jama.2008.623
|View full text |Cite|
|
Sign up to set email alerts
|

Low-Dose Aspirin for Primary Prevention of Atherosclerotic Events in Patients With Type 2 Diabetes<subtitle>A Randomized Controlled Trial</subtitle>

Abstract: clinicaltrials.gov Identifier: NCT00110448.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
408
0
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 704 publications
(425 citation statements)
references
References 32 publications
9
408
0
8
Order By: Relevance
“…In the Japanese Primary Prevention of Atherosclerosis with Aspirin for Diabetes trial, 2539 patients with diabetes mellitus and no history of atherosclerosis were randomly assigned to low-dose aspirin or no treatment. 154 The primary end point of fatal and nonfatal heart events, fatal and nonfatal stroke events, and peripheral artery disease was not significantly different between the groups. Similarly, in the Prevention of Progression of Arterial Disease and Diabetes trial of 1276 patients with diabetes mellitus and peripheral artery disease diagnosed by an ankle brachial index <0.99, low-dose aspirin did not significantly reduce the primary composite end point of death from coronary heart disease or stroke, nonfatal…”
Section: Antiplatelet Therapymentioning
confidence: 81%
“…In the Japanese Primary Prevention of Atherosclerosis with Aspirin for Diabetes trial, 2539 patients with diabetes mellitus and no history of atherosclerosis were randomly assigned to low-dose aspirin or no treatment. 154 The primary end point of fatal and nonfatal heart events, fatal and nonfatal stroke events, and peripheral artery disease was not significantly different between the groups. Similarly, in the Prevention of Progression of Arterial Disease and Diabetes trial of 1276 patients with diabetes mellitus and peripheral artery disease diagnosed by an ankle brachial index <0.99, low-dose aspirin did not significantly reduce the primary composite end point of death from coronary heart disease or stroke, nonfatal…”
Section: Antiplatelet Therapymentioning
confidence: 81%
“…The controversy focuses on recent trials of at‐risk subgroups and the balance between benefit and risk. One clinical trial, which was conducted in Japan and focused on diabetes, failed to find significant differences, although the study was underpowered 31. The American Heart Association, in recent scientific statements, emphasized stricter criteria for aspirin use in high‐risk individuals balancing benefits and harm 8, 9, 10, 11.…”
Section: Discussionmentioning
confidence: 99%
“…The Action to Control Cardiovascular Risk in Diabetes (ACCORD) study showed that the combination of statins and lipid‐lowering drug did not achieve additional cardiovascular benefits, as compared with statins alone 32. The results of clinical trials using aspirin for the primary prevention of cardiovascular diseases in diabetic patients varied 33, 34; therefore, whether aspirin has a protective effect in the primary prevention of cardiovascular diseases in diabetes patients remains unclear. Nevertheless, a systematic review of multiple clinical trials demonstrated that among patients with T2DM and cardiovascular disease risk factors, aspirin showed a certain cardiovascular protective effect 35.…”
Section: Primary Secondary and Tertiary Diabetes Preventionmentioning
confidence: 99%